Targeting Anabolic Impairment in Response to Resistance Exercise in Older Adults with Mobility Impairments: Potential Mechanisms and Rehabilitation Approaches - Micah J. Drummond; Robin L. Marcus; Paul C. LaStayo (Journal of Aging Research)
Muscle atrophy is associated with healthy aging (i.e., sarcopenia) and may be compounded by comorbidities, injury, surgery, illness, and physical inactivity. While a bout of resistance exercise increases protein synthesis rates in healthy young skeletal muscle, the effectiveness of resistance exercise to mount a protein synthetic response is less pronounced in older adults. Improving anabolic sensitivity to resistance exercise, thereby enhancing physical function, is most critical in needy older adults with clinical conditions that render them “low responders”. In this paper, we discuss potential mechanisms contributing to anabolic impairment to resistance exercise and highlight the need to improve anabolic responsiveness in low responders. This is followed with evidence suggesting that the recovery period of resistance exercise provides an opportunity to amplify the exercise-induced anabolic response using protein/essential amino acid ingestion. This anabolic strategy, if repeated chronically, may improve lean muscle gains, decrease time to recovery of function during periods of rehabilitation, and overall, maintain/improve physical independence and reduce mortality rates in older adults.